1986
DOI: 10.1002/cne.902440310
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y innervation of the hippocampal region in the rat and monkey brain

Abstract: Using antibodies to neuropeptide Y (NPY) in combination with immunohistochemical techniques we have studied the distribution of cell bodies and nerve terminals containing NPY immunoreactivity (-i) in the hippocampal region of rats and monkeys (cynomolgus). In colchicine-pretreated rats a large number of NPY-positive cells are present in all areas of the hippocampal region. The NPY-i cells range in size from small (diameter across soma: 10-15 micron) to large (approximately 20 micron). Most of the NPY-i cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(96 citation statements)
references
References 60 publications
9
87
0
Order By: Relevance
“…Similarly, in the in vitro models of ictal activity such as the stimulus train-induced bursting (STIB; 30) and related models (31), the primary afterdischarge mimics the tonicclonic characteristics of limbic seizures and responds to clinically effective concentrations of anticonvulsants (AEDs) that are effective on complex partial seizures (32). NPY, peptide YY (PYY), and the Y 2 receptor-selective agonist, [ahx [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ]NPY, potently inhibited the afterdischarge (29; see later for details about NPY receptors), whereas the Y 1 and Y 5 receptor-preferring ligand, Leu 31 , Pro 34 NPY was without effect on the afterdischarge in this model (29,33), suggesting the importance of the Y 2 receptor in NPY action (see later). Finally, NPY has been tested in slices of the frontal neocortex against seizure activity induced by a 0-Mg 2 ϩ solution.…”
Section: Epilepsy Models In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the in vitro models of ictal activity such as the stimulus train-induced bursting (STIB; 30) and related models (31), the primary afterdischarge mimics the tonicclonic characteristics of limbic seizures and responds to clinically effective concentrations of anticonvulsants (AEDs) that are effective on complex partial seizures (32). NPY, peptide YY (PYY), and the Y 2 receptor-selective agonist, [ahx [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ]NPY, potently inhibited the afterdischarge (29; see later for details about NPY receptors), whereas the Y 1 and Y 5 receptor-preferring ligand, Leu 31 , Pro 34 NPY was without effect on the afterdischarge in this model (29,33), suggesting the importance of the Y 2 receptor in NPY action (see later). Finally, NPY has been tested in slices of the frontal neocortex against seizure activity induced by a 0-Mg 2 ϩ solution.…”
Section: Epilepsy Models In Vitromentioning
confidence: 99%
“…Our laboratory recently tested this question by using a newly developed antagonist to the Y 2 receptor, BIIE 0246 (50), which profoundly reduced the presynaptic response to NPY and to the selective Y 2 -receptor agonist, [ahx [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ]NPY (51). Indeed, 30 n M BIIE 0246 reduced the effect of NPY in area CA1 of hippocampal slices to 40% of control levels (52; Fig.…”
Section: Genetic Manipulation Of Npy and Receptor Expressionmentioning
confidence: 99%
“…It contains numerous NPY interneurons and is rich in mGluRs (Kohler et al, 1986;Redrobe et al, 1999;Dumont et al, 1998). It was revealed that the enhancement of glutamatergic transmission strongly stimulated NPY synthesis and/or increased the content of that peptide in the hippocampus Bellmann et al, 1991;Schwarzer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…NPY is normally expressed very specifically in GABAergic neurons and not other cell types [6,7]. Fiber systems that innervate the dentate gyrus do not appear to express NPY.…”
Section: Normal Localization Of Npy and Its Receptors In The Rat Dentmentioning
confidence: 99%
“…However, there are some general rules that can be concluded. First, most of the cell bodies are located in the hilus and in the granule cell layer [7]. In addition, these neurons appear mostly to be "local circuit neurons" because their axon typically arborizes in the hippocampal lamella where the cell body is located.…”
Section: Normal Localization Of Npy and Its Receptors In The Rat Dentmentioning
confidence: 99%